1999
DOI: 10.1149/1.1392659
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dichromate Ions on Corrosion of Pure Aluminum and AA2024‐T3 in NaCl Solution Studied by AFM Scratching

Abstract: The localized corrosion of pure aluminum, AA2024-T3 alloy, and in particular the behavior of the intermetallic particles in AA2024-T3 were studied using a technique of scratching the surface with atomic force microscopy (AFM) tips. In situ AFM scratching provides information regarding the protectiveness of the surface film. Scratching of aluminum by rastering the surface with the AFM tip in contact mode in 0.5M NaCl resulted in accelerated uniform dissolution in the rastered area. Slow pumping of the solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(84 citation statements)
references
References 35 publications
2
81
0
1
Order By: Relevance
“…Scanning Kelvin probe force microscopy (SKPFM) was used to produce maps of the Volta potential distribution across surfaces of AA2024-T3 in air. [18][19][20][21] Used in conjunction with topographic measurements, SKPFM, which has a resolution of at least 100 nm, has generated considerable understanding of the role of intermetallic compounds on the corrosion behavior in terms of shape, location, and local practical nobility. Studies of the delamination of ultrathin (20-100 nm) plasma polymers on specially designed gold samples by SKPFM have shown a loss of spatial resolution of only about 10 µm attributable to sample/tip separation and electrical charging of the coating.…”
Section: Fontana Corrosion Center Department Of Materials Science Anmentioning
confidence: 99%
“…Scanning Kelvin probe force microscopy (SKPFM) was used to produce maps of the Volta potential distribution across surfaces of AA2024-T3 in air. [18][19][20][21] Used in conjunction with topographic measurements, SKPFM, which has a resolution of at least 100 nm, has generated considerable understanding of the role of intermetallic compounds on the corrosion behavior in terms of shape, location, and local practical nobility. Studies of the delamination of ultrathin (20-100 nm) plasma polymers on specially designed gold samples by SKPFM have shown a loss of spatial resolution of only about 10 µm attributable to sample/tip separation and electrical charging of the coating.…”
Section: Fontana Corrosion Center Department Of Materials Science Anmentioning
confidence: 99%
“…A great effort has been made to analyze the corrosion behavior of high strength aluminum alloys. In particular, AA2024-T3 is among the most extensively studied alloys, and the mechanisms of corrosion have been debated in the literature [5,[7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The goal of using SKPFM was to measure Volta potential differences between phases within the microstructure to determine relative nobility of the individual phases. Schmutz and Frankel, along with Leblanc, have established a direct correlation between Volta potentials measured in air and respective solution potentials of metals [26,27,30]. Importantly, the VPD observed was an effective indicator of how corrosion developed due to microstructural features.…”
Section: Discussionmentioning
confidence: 89%
“…SKPFM measurements were obtained prior to SEM/EDS characterization of the same regions on both braze alloy joints to avoid any effect of electron irradiation on surface potential measurements [22,26,27]. Potential maps acquired from SKPFM coupled with composition maps obtained from SEM/EDS clearly showed that the observed variations in potential correlated with changes in composition within the braze regions (Figures 8 and 9).…”
Section: Skpfm Measurementsmentioning
confidence: 97%
See 1 more Smart Citation